Aldeamentos indígenas em Sergipe Colonial: subsídios para a investigação de Arqueologia Histórica - Santana, Pedro Abelardo de (2004)
Indigenous villages in Colonial Sergipe: subsidies for the investigation of Historical Archaeology it is a master dissertation, based on historical documents and in literature. It synthesizes the knowledge produced on the villages indigenous of Sergipe, founded among the centuries 17 and 19. Taking as parameters theories and methodologies used by the Historical Archaeology, it recovers information and it formulates inquiries with the purpose of they be good as subsidies for future archaeological excavations in the sites of the old villages. They are outstanding aspects as its functions in the colonial society, its economy, the social and religious life, among others. The studied villages is: Geru, Água Azeda, Aracaju, Japaratuba, Pacatuba, São Pedro do Porto da Folha and Jacaré.